Roland Barthes and fashion: a reading based on the punctum and the studium (ModaPalavra e-periódico, 2021)
Based on two statements by Barthes, in La Chambre Claire, the first being the one in which he claims the punctum is the pinnacle of style, and the second the studium would be all that brings together generalized consensus, this study aims to establish the relation between these two concepts and the ideas of style and fashion. Thus, we seek to develop the correspondence between fashion and studium - emphasizing that the latter is close to the idea of ​​myth - and in the same way, that style is linked to the punctum - which is close to the idea of ​​writing. In addition, with the hypothesis of an articulation of the concepts within the Barthesian work, we also seek Barthes' look on the themes of style and fashion in his texts contained in the Inéditos Vol. III: Imagem e Moda, pointing out that the author who was one of the first to foresee the importance of fashion in contemporary society, including the strength of its mythology.
Keywords: fashion; style; punctum